TURISMO NO TERRITÓRIO PATAXÓ BARRA VELHA DO MONTE PASCOAL: ETNODESENVOLVIMENTO, ESPACIALIDADE E POLÍTICAS - Oliveira, Carlos Alfredo Ferraz de (2020)
Tourist visitation in territories of different indigenous peoples has been occurring for some decades in Brazil, showing diversified experiences in which the State has been challenged to comprehend and act. A practice that is constituted by multiple and c